2021
DOI: 10.1017/s0021932021000596
|View full text |Cite
|
Sign up to set email alerts
|

Age-appropriate feeding practices and their association with undernutrition among children aged 6–23 months in aspirational districts of India: a multinomial analysis

Abstract: ‘Health and nutrition’ is one among the five areas covered by the Aspirational District Programme in India, which aims to achieve the Sustainable Development Goals (SDGs). The reduction of undernutrition in under-five children has remained a major focus of the SDGs, especially at the ages of 6–23 months as this affects child development. This study used National Family Health Survey 2015–16 data to examine appropriate feeding practices and their associations with undernutrition among children aged 6–23 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The determinants of composite index of anthropometric failure among urban slum children in the present study were exclusive breast feeding not being provided for 6 months, fathers being illiterate, Calorie intake being deficient as per RDA and birth weight being <2.5kgs. According to the study's findings, infants who are exclusively breastfed have a lower risk of developing anthropometric failure which coincides with other studies such as Itishree Pradhan et al 20 . The author analyzed the feeding practices and their associations with under nutrition among children aged 6-23 months in the 124 districts of India and stated that appropriate breastfeeding lowered the odds of children being undernourished.…”
Section: Discussionsupporting
confidence: 90%
“…The determinants of composite index of anthropometric failure among urban slum children in the present study were exclusive breast feeding not being provided for 6 months, fathers being illiterate, Calorie intake being deficient as per RDA and birth weight being <2.5kgs. According to the study's findings, infants who are exclusively breastfed have a lower risk of developing anthropometric failure which coincides with other studies such as Itishree Pradhan et al 20 . The author analyzed the feeding practices and their associations with under nutrition among children aged 6-23 months in the 124 districts of India and stated that appropriate breastfeeding lowered the odds of children being undernourished.…”
Section: Discussionsupporting
confidence: 90%
“…Children of the first birth order had higher odds of having MDDF than the children of the second and third birth order. With the increase in maternal age and maternal education, children were less likely to experience MDDF, whereas the children of mothers with some exposure to mass media (aOR: 0⋅84, 95 % CI 0⋅78, 0⋅91, P < 0⋅001) and with four or more antenatal care (ANC) Recent studies (25,26) also identified that strengthening IYCF programmes would require intensive focused intervention to control MDDF in select districts, especially aspirational districts in high-focus group states in India. The present study presents the association of MDDF with a range of factors, including child, maternal, household and regional characteristics of children, their healthcare exposure and concurrent health status.…”
Section: Resultsmentioning
confidence: 99%
“…With developed states such as Kerala, Goa and Karnataka reporting an increase in MDDF between 2005–6 and 2015–16, as well as large clusters of districts with high MDDF covering highly populated states in India, poor IYCF practices among children in India seem widespread. Recent studies ( 25 , 26 ) also identified that strengthening IYCF programmes would require intensive focused intervention to control MDDF in select districts, especially aspirational districts in high-focus group states in India. The present study presents the association of MDDF with a range of factors, including child, maternal, household and regional characteristics of children, their healthcare exposure and concurrent health status.…”
Section: Discussionmentioning
confidence: 99%